Property Rights Problems in Agricultural Cooperatives: A Heterodox Institutionalist Perspective - Vladislav Valentinov; Constantine Iliopoulos (German Journal of Agricultural Economics (GJAE), 2012)
New institutional economists have identified a number of property rights problems in agricultural cooperatives. This paper reconsiders these problems from the perspective of heterodox institutionalist economics in the tradition of Veblen and Ayres. The property rights problems of agricultural cooperatives seemingly reinforce the new institutional economics presumption of the superiority of fully delineated private ownership. In contrast, the paper shows these problems to be likewise consistent with the heterodox institutionalist school, which is much more reserved about the societal role of private ownership. Toward this end, the paper elaborates the logical structure of the so-called "institutionalist dichotomy". The property rights problems of agricultural cooperatives are explained as a particular manifestation of this dichotomy.
Keywords: 330; Genossenschaft; Sachenrecht; Ländlicher Raum; Neue Institutionenökonomik